2003
DOI: 10.1046/j.1365-3083.2003.01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Less Sensitivity for Late Airway Inflammation in Males than Females in BALB/c Mice

Abstract: Several studies have investigated allergic airway inflammation, a T helper 2 (Th2)-type immune response, using a mouse model of asthma. At present, however, no reports have described sex differences in the sensitivity of late airway inflammation (LAI). The LAI induced by ovalbumin in adult BALB/c mice was compared in males and females or sham-operated males and castrated males. The males showed less severe bronchial-bronchiolar inflammation with infiltration of eosinophils and lymphocytes and lower content of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
101
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 32 publications
6
101
2
3
Order By: Relevance
“…Consistent with studies of allergic inflammation in mice (Hayashi et al, 2003), the maximum absolute numbers of eosinophils after allergen challenge in female guinea pigs was greater than males. In pulmonary function, adult male guinea pigs started with a higher airway resistance than adult females, but had similar increases in airway hyperresponsiveness after antigen challenge.…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with studies of allergic inflammation in mice (Hayashi et al, 2003), the maximum absolute numbers of eosinophils after allergen challenge in female guinea pigs was greater than males. In pulmonary function, adult male guinea pigs started with a higher airway resistance than adult females, but had similar increases in airway hyperresponsiveness after antigen challenge.…”
Section: Discussionsupporting
confidence: 84%
“…Hayashi and colleagues (24) reported less severe bronchialbronchiolar inflammation in allergic males compared with allergic females. Following castration, males were similar to females, suggesting a protective role for androgens in the development of allergic airway disease (24). Ovariectomized rats developed less airway inflammation compared with sham controls (35).…”
Section: Allergic Airway Diseasementioning
confidence: 89%
“…Several studies have reported an increased susceptibility to allergic airway disease in female mice compared with male mice (11,24,45,64). Corteling and Trifilieff (11) reported increased serum IgE in allergic female mice compared with male mice and that female mice were less sensitive to the therapeutic effects of the steroid budesonide.…”
Section: Allergic Airway Diseasementioning
confidence: 99%
“…Testosterone is secreted by ovaries and by the adrenal gland, and it appears to act as an immunosuppressive and anti-inflammatory, by decreasing the Th2-response via androgen receptor (by activating androgen responsive elements of target genes) (29). Studies show that the severity of asthma in men remains stable from puberty, until serum testosterone levels start to decease with aging (when higher asthma prevalence in men is observed) (30) and that castration in man exacerbates asthma (31). Consistent with our findings, Wulfsohn et al demonstrated (28) that female asthmatic patients treated with testosterone demonstrated a 90% improvement of asthma symptoms, while Mileva et al (25) found low levels of serum testosterone in patients with severe (when compared with mild) asthma.…”
Section: Discussionmentioning
confidence: 99%